Bahtsul Masa’il sebagai Upaya Mengembangkan Mental Santri - Mas’adah, Silvia; Nurfalah, Yasin (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The aim of this research is to know the role of knowing Lajnah Bahtsul Masa'il in sharpening the mentality of the students of the Tahfizhil Qur'an Lirboyo Islamic Boarding School, Kediri City. This research uses qualitative methods with techniques for collecting interview results, observation and documentation. The research results obtained are: First, the Lajnah Bahtsul Masa'il process uses team play by dividing tasks between each individual in the group. Second, there is a positive relationship between Lajnah Bahtsul Masa'il on the mental health of the students of the Tahfizhil Qur Islamic Boarding School. 'A. Every student who becomes an activist for Lajnah Bahtsul Masa'il has a better mentality. This can be seen according to the reality where the students who become ro'is in the average class of Lajnah Bahtsul Masa'il activism.